Estación Multimodal ''Nueva Ospina'' (2021)
A project with a heritage approach is proposed in which it seeks to recover the railroad in the region, carrying out a reinterpretation of the Ospina Station, which will be the municipality out of a focus as the capital of the department. It is generated by means of the above to evoke those social dynamics on culture, economy and development that 57 years ago were due to the use of the train in addition to having a means of transport that is more efficient than the current one, thus managing to solve problems of mobility, social dynamics that exist due to the sectorization of the municipality.